Wireless Mesh network secure routing mechanism based on dynamic reputation - Hongyu YANG; Yue HAN (Tongxin xuebao)
Aiming at the problem that the wireless Mesh network (WMN) security routing mechanism was scarce and internal malicious nodes drop data packets during data transmission,a secure routing mechanism based on dynamic reputation (SRMDR) for wireless Mesh network was proposed.Firstly,the dynamic reputation mechanism was used to evaluate the node’s behavior,the node’s comprehensive reputation value was calculated according to the node’s direct reputation value and the recommended reputation value,and the node’s dynamic reputation value was calculated according to the node’s historical comprehensive reputation value and the current comprehensive reputation value.Then,the dynamic reputation was combined with the routing mechanism to establish secure routing paths,the nodes with a dynamic reputation value less than the threshold were determined to be malicious nodes,which were isolated during the routing process.Experimental results show that compared with HWMP and SHaRP,SRMDR has higher malicious node recognition rates,and SRMDR can effectively reduce packet loss rate and improve network throughput.